Vitreous in Health and Disease - Sebag, J. (Springer New York : Imprint: Springer, 2014)
The vitreous body long has been the most mysterious of all ocular structures, owing perhaps to its seeming simplicity. There have been few concerted, sustained efforts to unravel the mysteries of how vitreous is composed and what role it plays in normal physiology as well as pathology. Over the years, however, many studies have produced important findings concerning vitreous biochemistry, structure, physiology, and pathobiology. Published on the 25th anniversary of Sebag's first book on Vitreous, this second installment is nearly five times longer than its predecessor, reflecting how much has been learned in the past quarter century. This well-constructed compendium not only addresses the most current scientific knowledge, but also reviews clinical perspectives in a manner that lends richness to the scope of the book. Written by 90 authors, this book has 56 chapters organized into 7 sections: Biochemistry; Anatomy, Development, and Aging; Pathology/Pathobiology; Physiology and Phamacotherapy; Posterior Vitreo-Retinal Surgery; Peripheral Vitreo-Retinal Surgery; and Pharmacologic Vitreolysis. With a foreword by Coleman & Lincoff and an introduction by Wallace Foulds, Sebag's latest tome on vitreous is destined to be the authoritative text for years to come.